Measurement of the effective $B^0_s→ K^+K^-$ lifetime - Collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; et al. (2011)
A measurement of the effective $B^0_s→ K^+K^-$ lifetime is presented using approximately $37 pb^{-1}$ of data collected by LHCb during 2010. This quantity can be used to put constraints on contributions from processes beyond the Standard Model in the $B^0_s$ meson system and is determined by two complementary approaches as $τ_{B^0_s→ K^+K^-} = 1.440 ± 0.096 (stat) ± 0.008 (syst) ± 0.003 (model) ps$.